Bactérias solubilizadoras de fosfato na cultura da soja - Vey, Rosana Taschetto (2023)
Phosphorus (P) is an essential nutrient for plants, being one of the main elements for food production, however, part of the total added to the soil becomes unavailable to plants. The addition of phosphate-solubilizing bacteria has been identified as a viable way to increase the availability of adsorbed P in the soil to plants and promote plant growth. However, the real potential depends on which species of microorganisms are involved and the interaction with local soil and climate factors, and scientific investigation is essential for the effective advance in the state of the art on the subject. The objective of this research was to evaluate the benefits of growth-promoting bacteria in the soybean crop, and also, the ability of phosphate solubilization in the soil by the action of these bacteria. In the first chapter, three experiments were carried out in the field, using growth-promoting bacteria under different doses of P in the soil. In the second chapter, the ability of these microorganisms to carry out the solubilization of phosphates in the laboratory was evaluated, and also, an experiment was carried out in hydroponics to quantify the absorption of P by soybean leaves. It is concluded with this research that the use of bacteria belonging to the genus Pseudomonas sp. (BAC 71) promoted a higher concentration of P in the roots and in the aerial part of the soybean crop, in addition to greater length, area and root volume. This bacterium can be used in future research as a possible phosphate solubilizing bacterium in the soil in addition to promoting growth. The bacterium Bacillus subtilis promoted higher dry mass and higher concentration of phosphorus in soybean leaves, in addition, this bacterium also showed an average phosphate solubilization index, which is considered an alternative for better use of this nutrient in the soil.